Área de proteção ambiental da Barra do Rio Mamanguape: análise das práticas tradicionais e do turismo de base comunitária - Valencia, Carlos Alberto Isaza (2021)
Conservation Units are generally territories occupied by rural communities that sustain their economy from traditional production systems. These territories attract the attention of those interested in ecological tourism, favoring the creation of new economic dynamics and activities with the potential to promote community social development. This study is justified by the analysis of the natural elements that support the economy, understanding the role of Ecosystem Services (ES) and associative practices, in favor of social development. In this order of ideas, this dissertation has as its object of study the socioeconomic practices of the inhabitants of the Barra de Mamanguape Environmental Protection Area and Area of Relevant Ecological Interest (APA BRM). The general objective is to analyze tourism and the traditional practices that take place at APA BRM, guided from the theories of Ecosystem Services and Solidarity Economy (EcoSol). According to the hypotheses outlined, the ES promote the economic independence of this community, through associative practices linked to ecosystems. Different data collection and analysis techniques were adopted: direct and participant observation, questionnaires, semi-structured interviews; informal conversations, oral historical accounts, and participatory social cartography. As a result, it is concluded that the traditional practices of this community are associative activities by nature and are carried out in a sustainable manner, ensuring social development. It was also found that conscientious driving, which incorporates the observation of natural species and landscapes, has elements of environmental education through local ecological knowledge. In this way, the use of ES linked to traditional production systems and TBC can be classified as EcoSol, with the potential to allow economic independence for communities.